Between Court and Village: The Evolution of Aristocratic Spaces in Early Modern Spain - Martínez Hernández, Santiago (Renaissance and Reformation / Renaissance et Réforme, 2020)
In May 1561, King Philip II informed the town hall of Madrid that he had chosen their town as the site for his royal residence and court. That year, the city was swiftly transformed into the Catholic king’s court and the heart of his vast monarchy. It also became the principal political and cultural space for the nobility. Yet the greatest noble houses, particularly those in Castile, were initially resistant to the establishment of a sedentary royal court and continued to exercise and represent their status at their own traditional courts. Increasingly, however, they were obliged to reside in Madrid in order to ensure direct access to the king’s grace and favour. Throughout the seventeenth century, the Spanish aristocracy became courtiers through necessity rather than conviction. In response to this situation, and without neglecting their noble estates and interests, they created their own spaces at court, and over time were able to colonize the royal capital and convert it into their own natural habitat.